Measuring the Level of Cognitive Insight of the high school students - Shehab, Mona Mohamad; Saleh, Amer Mahdi (Journal of Tikrit University for Humanities, 2023)
The study aims to reveal the level of cognitive clairvoyance in high school students and identify the moral differences according to the gender variable in a sample of secondary school students. The research sample has attracted 300 students and the researcher has built a measure of cognitive clairvoyance as the scale is 24 paragraphs and the data has been processed using the statistical bag (SPSS ). The results of the research showed the presence of a statistically significant difference in the level of cognitive foresight in high school students and the results also showed the presence of a statistically significant difference in the Cognitive clairvoyance according to the gender variable (male/female) and in favor of males.